Ambulatory blood pressure trajectories and blood pressure variability in kidney transplant recipients: a comparative study against chronic kidney disease patients - Maria Korogiannou; Marieta Theodorakopoulou; Pantelis Sarafidis; Maria Eleni Alexandrou; Eva Pella; Efstathios Xagas; Antonis Argyris; Athanase Protogerou; Aikaterini Papagianni; Ioannis N. Boletis; Smaragdi Marinaki (The Korean Society of Nephrology, 2022)
Background Hypertension is a major cardiovascular risk factor in both kidney transplant recipients (KTRs) and patients with chronic kidney disease (CKD). Ambulatory blood pressure monitoring (ABPM) is considered the gold-standard method for hypertension management in these subjects. This is the first study evaluating the full ambulatory blood pressure (BP) profile and short-term BP variability (BPV) in KTRs versus CKD patients without kidney replacement therapy. Methods Ninety-three KTRs were matched with 93 CKD patients for age, sex, and estimated glomerular filtration rate. All participants underwent 24-hour ABPM. Mean ambulatory BP levels, BP trajectories, and BPV indices (standard deviation [SD], weighted SD, and average real variability) were compared between the two groups. Results There were no significant between-group differences in 24-hour systolic BP (SBP)/diastolic BP (DBP) (KTRs: 126.9 ± 13.1/79.1 ± 7.9 mmHg vs. CKD: 128.1 ± 11.2/77.9 ± 8.1 mmHg, p = 0.52/0.29), daytime SBP/DBP and nighttime SBP; nighttime DBP was slightly higher in KTRs (KTRs: 76.5 ± 8.8 mmHg vs. CKD: 73.8 ± 8.8 mmHg, p = 0.04). Repeated measurements analysis of variance showed a significant effect of time on both ambulatory SBP and DBP (SBP: F = [19, 3002] = 11.735, p < 0.001, partial η2 = 0.069) but not of KTR/CKD status (SBP: F = [1, 158] = 0.668, p = 0.42, partial η2 = 0.004). Ambulatory systolic/diastolic BPV indices were not different between KTRs and CKD patients, except for 24-hour DBP SD that was slightly higher in the latter group (KTRs: 10.2 ± 2.2 mmHg vs. CKD: 10.9 ± 2.6 mmHg, p = 0.04). No differences were noted in dipping pattern between the two groups. Conclusion Mean ambulatory BP levels, BP trajectories, and short-term BPV indices are not significantly different between KTRs and CKD patients, suggesting that KTRs have a similar ambulatory BP profile compared to CKD patients without kidney replacement therapy.